2014
DOI: 10.4239/wjd.v5.i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design and baseline patient characteristics of the optimal type 2 diabetes management including benchmarking and standard treatment study in Greece

Abstract: Despite relevant treatment, there is a poor control of diabetes, hypertension and hyperlipidemia in Greek outpatients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the GLANCE study, the LDL-C target was achieved by 57% of subjects, compared to 31% [15] and 60% [36] in previous Greek studies. In addition, adequate SBP control was achieved in the GLANCE study by 55% of subjects compared to a previously reported rate of 27% [15], while the composite metabolic control rate was 22% in this work compared to about 5% in a previous study [15]. Arguably, our results point to some improvement-or at least some degree of stability-in the observed rates compared to those reported previously.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In the GLANCE study, the LDL-C target was achieved by 57% of subjects, compared to 31% [15] and 60% [36] in previous Greek studies. In addition, adequate SBP control was achieved in the GLANCE study by 55% of subjects compared to a previously reported rate of 27% [15], while the composite metabolic control rate was 22% in this work compared to about 5% in a previous study [15]. Arguably, our results point to some improvement-or at least some degree of stability-in the observed rates compared to those reported previously.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies have reported glycaemic control rates of 53-67% [15,30,37]. In the GLANCE study, the LDL-C target was achieved by 57% of subjects, compared to 31% [15] and 60% [36] in previous Greek studies. In addition, adequate SBP control was achieved in the GLANCE study by 55% of subjects compared to a previously reported rate of 27% [15], while the composite metabolic control rate was 22% in this work compared to about 5% in a previous study [15].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In Greece, more than 2 thirds of patients with T2DM receiving anti-hyperglycaemic monotherapy are treated with metformin [16], which is in alignment with the HDA treatment guidelines [4]. However, 32.9 % to 47.0 % of actively treated patients have HbA 1c levels ≥ 7 % ( ≥ 53 mmol/mol) for significant periods of time [17,18]. In the Europe-wide PANORAMA study, which included Greece, one of the barriers to glycaemic control attainment is clinical inertia [19].…”
Section: Introductionmentioning
confidence: 99%